Synthesis and primary anticonvulsant activity evaluation of 6-alkyoxyl-tetrazolo[5,1-a]phthalazine derivatives - Sun, Xian-Yu; Wei, Cheng-Xi; Deng, Xian-Qing; Sun, Zhi-Gang; Quan, Zhe-Shan (Arzneimittelforschung, 2010)
A new series of 6-alkyoxyl-tetrazolo[5,l-a] phthalazine derivatives (4 a-4 o) were synthesized as potential anticonvulsant agents. Anticonvulsant activity was evaluated by the maximal electroshock (MES) test. Neurotoxicity was evaluated by the rotarod neurotoxicity test. The pharmacological results showed that 6-(4-chlorophenyoxyl) - tetrazolo [5,1-a] phthalazine (4 m) was the most potent agent, with a median effective dose (ED50) of 6.8 mg/kg and a median neurotoxic dose (TD50) of 456.4 mg/kg. The protective index (PI = TD50/ED50) for compound 4 m was 67.1, which was significantly higher than that for the reference drug carbamazepine (PI = 6.4).
Keywords: Antiepileptic drugs; Maximal electroshock; Phthalazine derivatives, anticonvulsant activity; Tetrazole